Keynesian Economics - Timlin, Mabel F. (Mabel Frances) (Book collections on Project MUSE., 1942)
It is the intention in this study to explore the system of economic analysis set out in its original form in Mr. John Maynard Keynes' The General Theory of Employment, Interest and Money in order to consider first its internal consistency and second its application to the world we know.